Lewis Lung Cancer Cells Promote SIGNR1(CD209b)‐Mediated Macrophages Polarization Induced by IL‐4 to Facilitate Immune Evasion. Issue 5 (2nd November 2015) - Yan, Xiaolong; Li, Wenhai; Pan, Lei; Fu, Enqing; Xie, Yonghong; Chen, Min; Mu, Deguang
ABSTRACT: Tumor‐associated macrophages are a prominent component of lung cancer and contribute to tumor progression by facilitating the immune evasion of cancer cells. DC‐SIGN (CD209) assists in the immune evasion of a broad spectrum of pathogens and neoplasms by inhibiting the maturation of DCs and subsequent cytokines production. However, the expression of DC‐SIGN in macrophages and its role in mediating immune evasion in lung cancer and the underlying mechanism remain unclear. Our study aimed to identify the immunosuppressive role of SIGNR1 in murine macrophage differentiation and lung cancer progression. We found that SIGNR1‐positive RAW264.7 macrophages were enriched in mixed cultures with Lewis lung cancer cells (LLC) (ratio of RAW 264.7 to LLC being 1:1) after stimulation with IL‐4. Moreover, LLC‐educated macrophages exhibited significantly higher levels of IL‐10 but lower IL‐12 in response to IL‐4 treatment as determined by RT‐PCR and ELISA. However, inhibition of SIGNR1 markedly hampered the production of IL‐10, indicating that SIGNR1 was indispensable for IL‐4+LLC induced macrophage polarization towards the M2 subtype. Furthermore, polarized M2 cells immersed in a tumor microenvironment promoted the migration of LLCs, as measured by transwell assays, but migration was suppressed after blockade of SIGNR1 using CD209b antibody. In addition, IL‐4+LLC‐educated macrophages reduced the proliferation of the activated T cells and reduced IFN‐γ‐mediated Th1 response in T cells, while SIGNR1 inhibition rescued Th1 cell functions. In conclusion, murine SIGNR1 expressed in LLC‐educated macrophages appears to mediate IL‐4‐induced RAW264.7 macrophage polarization and thus facilitate lung cancer evasion. J. Cell. Biochem. 117: 1158–1166, 2016. © 2015 Wiley Periodicals, Inc.